2012
DOI: 10.1111/j.1743-6109.2012.02759.x
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Recovery of Erectile Function in Rat After Discontinuation of Dual 5-Alpha Reductase Inhibitor Therapy

Abstract: Aim The association of 5-alpha reductase inhibitor (5ARI) therapy and sexual dysfunction has been reported. Some patients claim persistent erectile dysfunction despite long-term discontinuation of 5ARI treatment. The aim of this study was to assess erectile function after cessation of 5ARI therapy using a rat model. Methods Twenty-six adult male Sprague-Dawley rats were randomized into three groups: (i) control (N = 10); (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 35 publications
2
32
0
Order By: Relevance
“…An editorial following the report by Belknap [89] has highlighted the need to re-think the safety of these drugs [90]. The following section summarizes preclinical and clinical evidence documenting how finasteride and dutasteride may impair sexual function, including sexual desire, erectile, ejaculation and orgasmic function [23,[91][92][93][94][95].…”
Section: Adverse Effects On Sexual Functionmentioning
confidence: 96%
See 2 more Smart Citations
“…An editorial following the report by Belknap [89] has highlighted the need to re-think the safety of these drugs [90]. The following section summarizes preclinical and clinical evidence documenting how finasteride and dutasteride may impair sexual function, including sexual desire, erectile, ejaculation and orgasmic function [23,[91][92][93][94][95].…”
Section: Adverse Effects On Sexual Functionmentioning
confidence: 96%
“…Öztekin et al, [95] and Pinsky et al, [94] demonstrated that treatment of mature animals with dutasteride resulted in reduced serum 5α-DHT levels by~86.5 % after 30 days. A significant decrease in the intracavernosal pressure (ICP) was recorded in animals treated with dutasteride.…”
Section: Adverse Effects On Sexual Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…Treatment of mature male animals with dutasteride produced significant reductions in the intracavernosal pressure (ICP) [40,41]. Electrical field stimulation (EFS) or acetylcholine-induced smooth muscle relaxation was significantly attenuated in corpus cavernousm tissues from dutasteride-treated animals [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is conceivable that inhibition of 5α-Rs may result in serious sexual adverse effects during the treatment and even after cessation of the treatment due to the complex mechanism of these enzyme reactions [6][7][8]. Pre-clinical studies provided biochemical and physiological evidence for a role for 5α-dihydrotestosterone (5α-DHT) in erectile physiology [40][41][42]. A number of studies demonstrated that the effects of androgens on erectile physiology were likely mediated by the 5α-reduced metabolite, 5α-DHT [43][44][45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%